Do Competitive Contexts Affect Mindreading Performance? - Colle, Livia; Dimaggio, Giancarlo; Carcione, Antonino; Nicolò, Giuseppe; Semerari, Antonio; Chiavarino, Claudia (Frontiers in Psychology, 2020)
Mindreading is contingent upon interpersonal context. Effects of attachment contexts on mindreading have been studied extensively; however, little is currently known about how competitive contexts influence mindreading skills. The idea was that the capacity to think about mental states would decline when individuals experiencing failure in competition. This study aims to assess effects of a competitive experience (a computer competitive PC game) on a sample of healthy subjects (119 participants). The sample was divided into two sub-samples. The experimental group underwent an experience of failure, consisting in a PC game of logic against a hypothetical opponent whose level of abilities was described as similar to the participant. Individuals in the experimental group were informed when game was over that they had lost to their opponents. The control group, composed of 53 individuals, was required instead only to discuss past personal experiences of competitive interactions. The Metacognitive Assessment Interview was administered to each sub-sample for evaluating mindreading capacities. Self-report tests were additionally provided for evaluation of trait-based dispositions: self-esteem, perfectionism, narcissism. Results supported our hypothesis: induction of sense of failure compromises ability to describe one’s own mental states and mental states of others. This effect was more pronounced in the domain of self-reflection. Results remained significant after controlling for self-esteem, perfectionism and narcissism. We discuss possible clinical implications of these findings and the importance of evaluating mindreading capacities under the pressure of social rank as well as of other social motive.